The Fear of Covid-19 Scale (FCV-19S) in Spain: Adaptation and Confirmatory Evidence of Construct and Concurrent Validity - Begoña Espejo; Irene Checa (Mathematics, 2021)
Fear of the coronavirus has important implications on mental health. In western countries, a significant degree of vaccination has been achieved, but in Spain, less than 75% of the population has received both doses. The current situation is still seen as a threat by many people. Therefore, it is important to have reliable and valid measurement instruments to assess the impact of COVID-19 on the population. In this study, the Fear of COVID-19 Scale has been adapted to Spain, and its psychometric properties have been studied in a Spanish sample using Structural Equation Modeling. This methodology allows obtaining more reliable estimates, regardless of the measurement scale of the variables. The unifactorial structure was confirmed. The correlations with Neuroticism were statistically significant, and the concurrent validity structural equation model yielded good fit indices. However, neither age nor belonging to a risk group directly predict fear of the coronavirus in this sample, but gender and neuroticism are direct predictors. Likewise, neuroticism mediates the relationship between age and fear of COVID-19, and between gender and fear of COVID-19. So being young and being a woman show high scores on neuroticism, leading to their most intense fear of COVID-19. With this reliable and valid measurement instrument, it will be possible to assess the degree of fear of the coronavirus in the Spanish population and improve psychological interventions.